(untitled) (Bangladesh Medical Journal, 2021)
The study aimed to evaluate the association of recreational (habitual) physical activities with the osteoarthritis (OA) of the knee in the female. The case-control study was carried out at the Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in the year 2016 and 2017. The total participants were 174 female selected purposively with the age range of 40 – 70 years, among them 87 were the cases with OA of the knee, and the same number of the same age group were included as the control without OA of the knee. A structured interviewer-administered questionnaire was used to collect data. High level of physical activities (20 or more miles per week) was associated with OA of the knee, whereas moderate level of physical activities (10-20 miles/per week) and low level of physical activities (<10miles/per week) had no significant association with the OA of the knee. This study reveled the relationship of the physical activity and OA of the knee. Continue physical activity according to the public health guideline, may eliminate this such physical problem for the general health promotion and particularly to prevent the OA of the knee. Bangladesh Med J. 2019 Sep; 48 (3): 39-42